The effect of emotion regulation on risk-taking and decision-related activity in prefrontal cortex - Carmen Morawetz; Peter N. C. Mohr; Hauke R. Heekeren; Stefan Bode (Social Cognitive and Affective Neuroscience, 2019)
Emotion regulation impacts the expected emotional responses to the outcomes of risky decisions via activation of cognitive control strategies. However, whether the regulation of emotional responses to preceding, incidental stimuli also impacts risk-taking in subsequent decisions is still poorly understood. In this study, we investigated the interplay between the regulation of incidentally induced emotional responses and subsequent choice behavior using a risky decision-making task in two independent samples (behavioral and functional magnetic resonance imaging experiment). We found that overall, emotion regulation was followed by less risky decisions, which was further reflected in an increase in activation in brain regions in dorsolateral and ventrolateral prefrontal cortex and cingulate cortex. These findings suggest that altering incidental emotions using reappraisal strategies impacts on subsequent risk-taking in decision-making.
Keywords: 330; fMRI; neuroimaging; emotion regulation; reappraisal; valuation; cognitive control; decision-making; risk-taking